Kepuasan Nasabah Sebagai Mediasi Pada Pengaruh Benefits Offered Dan Penanganan Keluhan Terhadap Loyalitas - Adha, Mufti Alam Adha; Faiza Husnayeni Nahar; Robbyansah (Jurnal Manajemen dan Teknologi, 2025)
This research aims to examine the influence of the benefit offered and complaint handling on customer loyalty in using Sharia mobile banking, with customer satisfaction as a mediating variable. It analyses the factors that affect customer loyalty in the context of Sharia mobile banking. The research object is Sharia bank customers in the Special Region of Yogyakarta who actively use mobile banking services. The data were collected through an online questionnaire distributed to 100 respondents selected using purposive sampling. The research employs a quantitative approach with structural model analysis using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings indicate that both the benefit offered, and complaint handling have a positive impact of customer satisfaction. Furthermore, customer satisfaction serves as a mediating variable that strengthens the influence of these two factors on customer loyalty. These results highlight the critical role of satisfaction in fostering loyalty among users of Islamic banking services. Therefore, to enhance customer loyalty, Sharia banks should optimize the benefits provided through mobile banking and improve the quality of complaint and, alongside fast and responsive complaint handling that adheres to Sharia principles.